THE EFFECT OF BOKASHI FERTILIZER AND COATING SEEDS TOWARD THE SEED VIGOR AND SOYBEAN GROWTH - Dilla Nitra Gustiana; Sumadi Sumadi; Erni Suminar (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2018)
This study was aimed atdetermining the dosage of bokashi fertilizer and seed coating which can have an influence both on seed vigor and soybean growth. The experimental design used was Factorial Randomized Group Design consisting of two factors, namely the administration of three levels of bokashi fertilizer and seed coating with Thiamethoxam and Trichoderma which consisted of five levels. The combination of the two factors contained 15 treatments which were repeated three times. DSAASTAT application was used in the further testing. The implementation of the research includes: power testing, weighing, seed vigor test, land preparation, application of bokashi fertilizer, planting, maintenance, destruction, main observations and supporting observations. The results showed that there was no effect of interaction between bokashi fertilizer and seed coating on seed vigor and growth of Anjasmoro cultivar soybeans. Giving 300 g / polybag of bokashi fertilizer can increase soybean plant growth. Coating with Trichoderma sp. 1 g / 100 seeds is the best dose of seed vigor, but the treatment without seed coating is not significantly different from other seed coating treatmentsPENGARUH PUPUK BOKASHI DAN PELAPISAN BENIH TERHADAP VIGOR BIBIT DAN PERTUMBUHAN KEDELAIPenelitian ini bertujuan untuk menentukan dosis pupuk bokashi dan pelapisan benih yang dapat memberikan pengaruh baik pada vigor bibit dan pertumbuhan kedelai. Rancangan percobaan yang digunakan yaitu Rancangan Acak Kelompok Faktorial yang terdiri dari dua faktor yaitu pemberian pupuk bokashi tiga taraf dan pelapisan benih dengan Thiamethoxam dan Trichoderma sp. yang terdiri dari lima taraf. Kombinasi dari kedua faktor terdapat 15 perlakuan yang diulang tiga kali. Uji lanjut menggunakan aplikasi DSAASTAT. Pelaksanaan penelitian meliputi:uji daya, penimbangan, uji vigor bibit, persiapan lahan, aplikasi pupuk bokashi, penanaman, pemeliharaan, destruksi, pengamatan utama, dan pengamatan penunjang. Hasil penelitian menunjukkan bahwa tidak ada pengaruh interaksi antara pemberian pupuk bokashi dan pelapisan benih terhadap vigor bibit dan pertumbuhan kedelai kultivar Anjasmoro. Pemberian pupuk bokashi osis 300 g/polybag dapat meningkatkan pertumbuhan tanaman kedelai. Pelapisan dengan Trichoderma sp. 1 g/100 butir benih merupakan dosis terbaik terhadap vigor bibit. Namun, perlakuan tanpa pelapisan benih tidak berbeda nyata dengan perlakuan pelapisan benih lainnya.